The variability of physical enjoyment, physiological responses, and technical-tactical performance according to the bout duration of small-sided games: a comparative study between female and male soccer players - Zouhaier Farhani; Sofiene Amara; Mohamed Ben Aissa; Noomen Guelmami; Anissa Bouassida; Ismail Dergaa (BMC, 2024)
Abstract Background This study aimed to compare various factors, namely perceived enjoyment (PE), percentage of peak heart rate (%HRpeak), blood lactate (La), rating of perceived exertion (RPE), and technical-tactical performance among soccer players across different bout durations (CB: continuous bout, MIB: medium intermittent bouts, and SIB: short intermittent bouts) and between male and female players during four-a-side (4vs4) small-sided games (SSGs) including goalkeepers. Methods sixteen female soccer players (age: 20.1 ± 0.5 years old) and sixteen professional male adults (age: 20.7 ± 0.7 years old) participated in the study. SSGs (4vs4) were performed in a CB: (1 × 12 min), and in an interval format: MIB: (2 × 6 min), and SIB: (3 × 4 min) with 2 min of passive recovery. PE was collected after each SSGs. The players' heart rate (HR) was continuously measured, whereas ratings of perceived exertion (RPE) and, blood lactate concentration ([La]) were determined at the end of each SSGs. Technical-tactical performance were analyzed during each session of SSGs. Pitch dimensions were (length x width) (25 × 32 m), and relative space per players was 100 m2. Results For female soccer players, medium intermittent bouts (MIB) elicited significantly higher perceived enjoyment (PE) compared to continuous bouts (CB) (p < 0.001) and short intermittent bouts (SIB) (p < 0.01). Conversely, for male soccer players, CB resulted in higher PE compared to MIB (p < 0.001) and SIB (p < 0.001). During CB and MIB, peak heart rate (PeakHR) and percentage of peak heart rate (%HRpeak) were significantly higher in female players compared to SIB (PeakHR: CB: p < 0.001; PeakHR: MIB: p < 0.01; %HRpeak: CB: p < 0.001; %HRpeak: MIB: p < 0.01). Blood lactate (La) and rating of perceived exertion (RPE) were significantly greater in CB compared to MIB (La: p < 0.001; RPE: p < 0.01) and SIB (La: p < 0.001; RPE: p < 0.001) for female players only. For male players, CB resulted in significantly higher PeakHR, %HRpeak, La, and RPE compared to MIB (peak HR: p < 0.01, dunb = 1.35; %HR: p < 0.01; La: p < 0.01; RPE: p < 0.01) and SIB (peak HR: p < 0,01; %HR: p < 0.01; RPE: md = 0.87, p < 0.05). Regarding technical-tactical performance, in female players, the % of successful passes, successful tackles, and successful duels were higher during SIB compared to CB (p < 0.01; p < 0.001; p < 0.001) and MIB compared to CB (p < 0.01; p < 0.001; p < 0.001), while ball loss was lower during SIB compared to CB (p < 0.001) and MIB compared to CB (p < 0.001). In male players, % of successful passes and tackles were higher during CB compared to MIB (p < 0.001 and p < 0.05) and SIB (p < 0.001 and p < 0.05), while CB had a lower % of ball loss compared to MIB (p < 0.01) and SIB (p < 0.001). There was no significant difference in the % of successful duels between the bouts for either gender. Conclusion This study showed a difference in physical enjoyment between male and female soccer players depending on the bout duration of SSGs. For that, trainers should consider intermittent bouts for female soccer players and continuous bouts for male soccer players when designing SSGs-based training in order to significantly improve PE, training load, and technical-tactical performance.